Clinical Efficacy of Hyaluronic Acid with Iodine in Hard-to-Heal Wounds - Jana Pecová; Vladimíra Rohlíková; Markéta Šmoldasová; Jan Marek (Pharmaceutics, 2023)
Hard-to-heal wounds do not heal spontaneously and need long-term care provided by specialists. That burdens the patients as well as the healthcare systems. Such wounds arise from several pathologies, which result in venous leg ulcers (VLU), diabetic foot ulcers (DFU), pressure ulcers (PU), or ulcers originating from post-surgical wounds (pSW). Given the complex nature of hard-to-heal wounds, novel treatments are sought to enable wound healing. We tested the clinical efficacy and applicability of fluid comprising hyaluronic acid and iodine complex (HA-I) in the treatment of hard-to-heal wounds. Patients (n = 56) with VLU, DFU, PU, or pSW hospitalised in multiple wound-care centres in the Czech Republic were treated with HA-I. Wound size, classically visible signs of infection, exudation, pain, and wound bed appearance were monitored for 12 weeks. The highest healing rate was in DFU (71.4%), followed by pSW (62.5%), VLU (55.6%), and PU (44.4%). Classical visible signs of infection were resolved within 8 weeks in all types of wounds. Wound bed appearance improved most noticeably in pSW and then in VLU. Exudation was lowered most significantly in DFU and pSW. The highest decrease in pain was in pSW and DFU. The treatment with HA-I successfully led to either complete closure or significant improvement in the wound’s healing. Therefore, the complex of hyaluronic acid and iodine is suitable for the treatment of hard-to-heal wounds of various aetiologies.